2019
DOI: 10.1038/s41929-019-0400-x
|View full text |Cite
|
Sign up to set email alerts
|

Rational strain engineering in delafossite oxides for highly efficient hydrogen evolution catalysis in acidic media

Abstract: The rational design of hydrogen evolution reaction (HER) electrocatalysts which are competitive with platinum is an outstanding challenge to make power-to-gas technologies economically viable. Here, we introduce the delafossites PdCrO 2 , PdCoO 2 and PtCoO 2 as a new family of electrocatalysts for the HER in acidic media. We show that in PdCoO 2 the inherently strained Pd metal sublattice acts as a pseudomorphic template for the growth of a strained (by +2.3%) Pd rich capping layer under reductive conditions. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(108 citation statements)
references
References 79 publications
5
103
0
Order By: Relevance
“…[ 119 ] Various strategies have been applied to boost catalytic activity of nonprecious composites, such as doping, [ 116c,120 ] specific nanostructure, [ 121 ] and other techniques. [ 122 ] Recently, ionic vacancies, including anodic vacancies, cationic vacancies, and mixed vacancies, have been explored for HER with satisfactory electrocatalytic activity. [ 64,123 ] Promising results indicate the great potential of vacancies on promoting electrocatalytic performance ( Table 2 ).…”
Section: Electrochemical‐related Reactionsmentioning
confidence: 99%
“…[ 119 ] Various strategies have been applied to boost catalytic activity of nonprecious composites, such as doping, [ 116c,120 ] specific nanostructure, [ 121 ] and other techniques. [ 122 ] Recently, ionic vacancies, including anodic vacancies, cationic vacancies, and mixed vacancies, have been explored for HER with satisfactory electrocatalytic activity. [ 64,123 ] Promising results indicate the great potential of vacancies on promoting electrocatalytic performance ( Table 2 ).…”
Section: Electrochemical‐related Reactionsmentioning
confidence: 99%
“…[21,22] Alloying TMs has many benefits,such as lower catalyst cost, optimization of electronic properties through induced strain effects,a nd different adsorption strengths of key reaction intermediates,all of which can boost catalytic activity at the atomic scale. [23][24][25] Cobalt (Co) is an abundant low-cost transition metal that is widely used in the hydrolysis of AB.However,metallic Co has poor HER catalytic activity due to its weak hydrogen bonding energy. [26][27][28] In contrast, the noble metal ruthenium (Ru) is an ideal HER catalysts,w ith the cost of Ru being approximately 1/3 that of Pt.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, more and more attention is now being paid to transition metals alloy‐based catalysts [21, 22] . Alloying TMs has many benefits, such as lower catalyst cost, optimization of electronic properties through induced strain effects, and different adsorption strengths of key reaction intermediates, all of which can boost catalytic activity at the atomic scale [23–25] …”
Section: Introductionmentioning
confidence: 99%
“…In light of rapid fossil fuel consumption, severe environmental pollution, and drastic climate change, hydrogen (H 2 ) evolution technologies are paid more attention, owing to the high energy density and environmental‐friendliness of H 2 . Among them, electrochemical water splitting (2H 2 O→2H 2 +O 2 ), as a well‐established and renewable‐driven electrolysis process, has tremendous potential for converting electricity from the intermittent sun, wind, and other renewable sources into clean chemical energy (H 2 ) . Although many studies have been reported, a huge challenge facing this scenario remains the design of highly efficient catalyst electrodes to improve sluggish kinetics of the oxygen evolution reaction (OER) .…”
Section: Figurementioning
confidence: 99%